STUDYING SILENCE IN POPULAR CULTURE - Jackson, Kathy Merlock; Lindvall, Terry (Dialogue, 6(1), 2019)
This article explains the impetus for and execution of a team-taught, interdisciplinary class in silence using popular culture materials and practices, such as silent film, music, meditation, and mime. The course identifies individuals as possessing characteristics of introversion and extraversion and explores the role of silence in the modern world, incorporating the following: (1) Foundations for the Study of Silence, (2) The History of Silence, (3) The Role of Silence in Spirituality, Creativity and Reflection, (4) Silence in Communication Study, (5) Silent Film and Silence in Film, (6) The Role of Silence in a Highly Technological, Mediated World, and (7) Student Research Presentations. The class made students aware of the media-rich environment in which they live as well as the choices they have to seek quiet.. Keywords: Popular Culture, Silence, Quiet, Introversion, Extraversion, Spirituality, Creativity, Silent Film, Meditation, Mime, Interdisciplinary, Undergraduate Teaching, Higher Education, Curriculum Development
Keywords: Type of access: Open Access